Edukasi “4 Pilar Gizi Seimbang” pada Remaja di Panti Asuhan Ainul Yaqin Kota Jambi - Hatussaadah, Siti Fati; Kurnia, Fitriyan (Prosiding Seminar Kesehatan Nasional, 2024)
Nutritional problems in adolescents have an impact on optimizing adolescent growth and development. The direct causes of malnutrition in adolescents are the unbalanced food consumed and the presence of infectious diseases. Teenagers are usually not good at consuming daily food so that their immunity becomes weaker and they can be susceptible to disease and can make them more susceptible to infection and can reduce their appetite which can lead to nutritional deficiencies. Nutrition education regarding the 4 Pillars of Balanced Nutrition is one effort to prevent nutritional problems in adolescents. At the Ainul Yaqin Orphanage, most people still don't know about the 4 Pillars of Balanced Nutrition. The aim of this community service activity is to provide education on the 4 Pillars of Balanced Nutrition. The series of activities will start from March 2024 to July 2024 at the Ainul Yaqin Orphanage, Jambi City. There were 14 participants present. The material is delivered using the lecture method using power point for ± 90 minutes including a question and answer session with the participants. Before and after education, a pretest and posttest are given which are carried out by activity participants. The results obtained were a change in the average pretest and posttest knowledge, namely 22.2 (46.4 to 68.6). Another expected output is the publication of service results in a Sinta-indexed community service journal.